Development of the Orchid Diversity Pocket Book in Mutis Natural Forest as a Student Learning Resource in Plant Botany Courses - Ni Putu Yuni Astiani Dewi; Muhammad Amran Shidik; Maria Paulin Saridewi (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to produce a product in the form of a pocket book on Orchid Diversity in the Mutis Natural Forest as a learning resource for fourth-semester students of the Biology Education Study Program, at the University of Timor in the Higher Plant Botany course. This study uses the development model of Borg and Gall which consists of ten stages, but in this study, it is only limited to 5 stages, namely conducting preliminary research (pre-survey), planning, developing product forms, conducting product trials, and make product revisions. The results of the validation by material expert validators and learning media experts showed that the pocket book did not require significant revision and the conclusion given by the material expert validator and media expert was that the Orchid Diversity pocket book in the Mutis Natural Forest was declared feasible to be tested on students. Based on the student questionnaire calculation data on individual trials and small group trials, it can be concluded that the Orchid Diversity pocket book in Mutis Natural Forest has not undergone significant revisions. After going through the validation stage by material expert validators and learning media experts as well as from the results of individual and small group product trials, the resulting Orchid Diversity Pocket Book in Mutis Natural Forest is valid and suitable to be used as a learning resource in the Higher Plant Botany course at the University of Timor